Customer satisfaction response to the implementation of service quality in the printing industry - You, Bee Wan (2001)
The business environment of the 2000's has been a shift in firm's emphasis away from transactional exchange toward service quality exchange. Many studies have demonstrated the effect on customer satisfaction and profitability of pursuing what has become know generically as Service Quality Performance. Service Quality may be very attractive for many markets, while its adoption is inappropriate without prior comprehension of its content. Once sufficient and adequate properties of the content are achieved, the next task facing an industrial marketing manager is to specify relevant attributes of the content that lead to the required set of outcomes. Confusion often arises on which attributes may well represent the operational content of Service Quality in the different type of industry. This research was to present an idea to this confusion or rather problem by analyzing the concept of Service Quality in the critical areas of the printing industry namely; reception service, ordering/schedule planning, sale service, quality service, delivery process and account system. Contrary to the expectations raised by other researchers, this research is to examine the relationship, if any, between the implementation of service quality variables and the impact towards customer satisfaction and the customers' company performance. A set of questionnaires were prepared according the research objectives and distributed to a number of valuable customers in different type of industry namely; consumer electronics, food, beverage & pharmaceutical, computer, rubber & petroleum and others industry in the state of Johor, Melaka, Negeri Sembilan, Selangor and Perak. However, only 75 valuable customers responded to the survey. The research aimed to explore and explain the extent of importance of the service quality variables in the 6 areas as perceived by valuable customers. The contribution of current study is two fold. Firstly, it provides a well-defined content of Service Quality variables in the printing industry and secondly, it provides an initial approach to operationalise the concept of Service Quality in the critical areas into the printing industry. The information gathered was analyzed using SPSS/PC software. The Chi-Square test (Pearson Product Moment Correlation Coefficient) was used to see the relationship between the implementation of service quality variables and the company performance of the customer. Based on the analysis of this research, the researcher found that a significant relationship existed between the implementation of service quality variables and the company performance of the customer. Thus, the researcher concludes that the purchase intention from valuable customers will show the company performance depends very much on the customer satisfaction as indicated by the services quality performance in the printing industry.